Lessons learned for pandemic preparedness in the neurodegenerative research and clinical fields: an advice report based on Parkinson’s disease as an example - Marije J. Splinter; Emily J. Henderson; Yoav Ben-Shlomo; Sirwan K. L. Darweesh; Pawel Sowa; Frank J. Wolters; Premysl Velek; Hannie J. E. M. Meijerink; Paulus Bakx; M. Arfan Ikram; Evelien I. T. de Schepper; M. Kamran Ikram; et al. (BMC Neurology)
Abstract Background A sustainable pandemic preparedness strategy is essential to ensure equitable access to healthcare for individuals with neurodegenerative diseases. Moreover, it is vital to provide clinicians and researchers in the neurodegenerative disease fields with resources and infrastructure to ensure continuity of their work during a (health) crisis. Methods We established an international collaboration between researchers, clinicians, and patient representatives from the Netherlands, Poland, and the United Kingdom. We co-created a pandemic preparedness plan primarily informed by examples from those affected by or working in the field of Parkinson’s disease, with potential application to other neurodegenerative diseases or the general population. This plan builds upon insights and experiences from four population-based studies during the COVID-19 pandemic. Between March and November 2023, we organised two hybrid meetings in Bristol (United Kingdom) and Rotterdam (the Netherlands), and two online meetings. Results Research recommendations included three core factors in questionnaire design during health crises: 1) using existing, validated questions, 2) questionnaire adaptability and flexibility, and 3) testing within and outside the research group. Additionally, we addressed burden of participation, and we advocated for robust data sharing practices, underlining the importance of regulatory measures extending beyond the COVID-19 pandemic. We also shared clinical perspectives, including strategies to mitigate social isolation; challenges in virtual versus in-person consultations; and systemic changes to recognise and prevent moral injury in healthcare professionals. Conclusion In this pandemic preparedness plan, we provide research and clinical recommendations tailored to the field of Parkinson’s disease, with broader relevance to other neurodegenerative diseases and the general population. This establishes an essential framework for setting up new studies and safeguarding research and clinical practices when a new pandemic or other (health) crisis emerges. Graphical Abstract